Carbon farming in the living soils of the Americas - Cerri, Carlos Eduardo Pellegrino; Cherubin, Maurício Roberto; Villela, João Marcos; Locatelli, Jorge Luiz; Carvalho, Martha Lustosa; Villarreal, Federico; de Castro Mello, Francisco Fujita; Ibrahim, Muhammad Akbar; Lal, Rattan (Frontiers in Sustainable Food Systems, 2024)
Soil represents Earth's largest terrestrial reservoir of carbon (C) and is an important sink of C from the atmosphere. However, the potential of adopting best management practices (BMPs) to increase soil C sequestration and offset greenhouse gas (GHG) emissions in agroecosystems remains unclear. Synthesizing available information on soil C sink capacity is important for identifying priority areas and systems to be monitored, an essential step to properly estimate large-scale C sequestration potential. This study brings an overview of thousands of research articles conducted in the Americas and presents the current state-of-the-art on soil C research. Additionally, it estimates the large-scale BMPs adoption impact over soil C dynamics in the region. Results indicated that soil C-related terms are widely cited in the literature. Despite that, from a total of 13 thousand research articles recovered in the systematic literature review, only 9.2% evaluated soil C (at any depth), and only 4.6% measured soil C for the 0-30 cm soil layer, mostly conducted in North and South America regions. Literature review showed a low occurrence of terms related to BMPs (e.g., cover cropping), suggesting a research gap on the subject.Estimates revealed that upscaling of BMPs over 30% of agricultural land area (334 Mha) of the Americas can lead to soil C sequestration of 13.1 (±7.1) Pg CO2eq over 20 years, offsetting 39% of agricultural GHG emissions over the same period. Results suggest that efforts should be made to monitor the impact of cropping system on soil C dynamics on the continents, especially in regions where data availability is low (e.g., Central, Caribbean, and Andean regions). Estimating the available degraded area for the continent and the soil C sequestration rates under BMPs adoption for Central, Andean, and Caribbean regions were major shortcomings encountered in our analysis. Thus, it is expected that some degree of uncertainty may be associated with the obtained results. Despite these limitations, upscaling of BMPs across the Americas suggests having great potential for C removal from the atmosphere and represents a global positive impact in terms of climate change mitigation and adaptation.